Clinical outcome following coronary angioplasty in dialysis patients: a case–control study in the era of coronary stenting. Issue 5 (1st May 2001) - Le Feuvre, C; Dambrin, G; Helft, G; Beygui, F; Touam, M; Grünfeld, J P; Vacheron, A; Metzger, J P
Abstract : BACKGROUND: Balloon coronary angioplasty has been reported to be ineffective in patients treated for end stage renal disease because of a high restenosis rate. OBJECTIVE: To compare the clinical outcome following coronary angioplasty with provisional stenting in dialysis versus non-dialysis patients. DESIGN: A case–control study. PATIENTS: Of 1428 consecutive patients who underwent coronary angioplasty, 100 (7%) were being treated for end stage renal disease. These were compared with 100 control patients matched for age, sex, coronary lesions, presence of diabetes mellitus, and rate of coronary stenting (40%). MAIN OUTCOME MEASURES: In-hospital and one year clinical outcome. RESULTS: The rates of procedural success (90% v 93%), in-hospital mortality (1% v 0%), stent thrombosis (0% v 0%), and Q wave myocardial infarction (0% v 1%) were similar in dialysis and non-dialysis patients. One year clinical outcome after coronary angioplasty was similar in the two groups in terms of clinical restenosis (31% v 28%) and myocardial infarction (6% v 2%), but cardiac death was more common in dialysed patients (11% v 2%, p < 0.03). CONCLUSIONS: Dialysis does not increase the risk of clinical restenosis after coronary angioplasty with provisional stenting. Coronary angioplasty is a safe and effective therapeutic procedure in selected dialysis patients with culprit lesions accessible to stenting. However, the one year survival is reduced in this high risk population.